2012
DOI: 10.1007/s10409-012-0046-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of split Hopkinson tension bar technique to the study of dynamic fracture properties of materials

Abstract: A novel approach is proposed in determining dynamic fracture toughness (DFT) of high strength steel, using the split Hopkinson tension bar (SHTB) apparatus, combined with a hybrid experimental-numerical method. The center-cracked tension specimen is connected between the bars with a specially designed fixture device. The fracture initiation time is measured by the strain gage method, and dynamic stress intensity factors (DSIF) are obtained with the aid of 3D finite element analysis (FEA). In this approach, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Without proper pulse shaping, it is difficult to achieve dynamic stress equilibrium in such materials because the specimen may fail immediately from its end in contact with incident bar when it is impacted by the incident bar. What's more, the rigid-impact-contact caused by the bar/striker will bring about high frequency bit noise in the dynamic tests [6,7]. In this experiment, we found that a combined disc shaped pulse shaper made from soft materials (copper and rubber) can be utilized to minimize the high frequency bit noise to obtain ideal results.…”
Section: Pulse-shaper Techniquementioning
confidence: 88%
“…Without proper pulse shaping, it is difficult to achieve dynamic stress equilibrium in such materials because the specimen may fail immediately from its end in contact with incident bar when it is impacted by the incident bar. What's more, the rigid-impact-contact caused by the bar/striker will bring about high frequency bit noise in the dynamic tests [6,7]. In this experiment, we found that a combined disc shaped pulse shaper made from soft materials (copper and rubber) can be utilized to minimize the high frequency bit noise to obtain ideal results.…”
Section: Pulse-shaper Techniquementioning
confidence: 88%
“…The air gun system is used to propel the striker tube. A detailed illustration of the working principle of the air gun system can be found in [22].…”
Section: Methodsmentioning
confidence: 99%
“…Displacements, velocities and rupture time measured by detection sensors attached to a SHPB were compared with 2D numerical simulations. (Xu et al, 2012) proposed a novel approach to determine dynamic fracture toughness of high strength steel 40Cr using the SHTB technique and an hybrid experimental-numerical method. For such a purpose, curves of dynamic stress intensity factor history were obtained by full-scale 3D finite element simulation and dynamic fracture toughness was determined according to the fracture-initiation time measured by strain gauge method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Representative examples of this particular methodology can be found in (Anderson and Rosakis, 2005;Joudon et al, 2014;Kalthoff, 1985;Rubio-González et al, 2008;Shuter, 2002;Xu et al, 2012;Yokoyama, 1993) Purely optical methods are also very extended since, in general, they are inertia free. The shadow optical method of caustics (Kalthoff, 1986;Manogg, 1964) was the first successful optical method.…”
mentioning
confidence: 99%